The wave metaphor in feminist historiography: debates, critiques, and alternatives (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2026)
The wave metaphor is the most widespread yet most contested device for accounting for the history of feminism. Its use has given rise to a set of debates around its strengths, limitations, and alternatives, which have met with limited reception in the Spanish-speaking world and from Latin American perspectives. This absence is particularly relevant given that the metaphor does not merely organize the historical account but delineates which expressions may be considered part of it. The article systematizes these debates by examining tensions with generational identifications, the hegemonic character of the narrative, objections to the logic of progress and retreat, challenges linked to androcentric and teleological frameworks, and the proposals that have been put forward to overcome these limitations. Based on this review, it is argued that the metaphor’s limitations do not lie in its contents but in the way a device originally forged for political identification came to be adopted as a periodization tool without sufficient reflection on what this operation entails for historiographical practice.
Keywords: wave metaphor; historiography of feminism; periodization; feminist narratives